Exploring the Influence of online marketing and its Impact on business in Post-Covid-19: A conceptual paper on Sabah tourism industry - Zurina Patrick; Geoffrey Harvey Tanakinjal; Alesia Sigang Gugkang; Andrew Saw Tek Wei (Human Resource Management Academic Research Society (HRMARS), 2025)
This conceptual paper explores the adoption of online marketing and its impact on business performance within Sabah’s tourism industry in the post-COVID-19 era. Sabah, one of Malaysia's most popular tourism destinations, experienced a significant decline in tourist arrivals due to the pandemic, leading to a severe economic downturn. As part of the recovery process, online marketing has become a critical tool for tourism businesses to re-engage with both domestic and international markets. The paper integrates the Unified Theory of Acceptance and Use of Technology (UTAUT) and Diffusion of Innovation (DOI) models to identify the key determinants influencing the adoption of online marketing tools in the tourism sector. Additionally, it incorporates firm age and developmental culture as moderating variables, offering a comprehensive framework to understand technology adoption at an organizational level. The study highlights the importance of factors such as performance expectancy, effort expectancy, facilitating conditions, social influence, relative advantage, observability and compatibility in influencing the decision to adopt digital marketing. The findings suggest that, while online marketing can significantly improve visibility and revenue, its successful adoption depends on addressing infrastructure challenges, enhancing digital literacy, and fostering a culture of innovation within organizations. This paper contributes to the literature on digital marketing adoption in tourism, particularly in underrepresented regions like Sabah, and provides practical recommendations for policymakers, businesses, and academia to support sustainable tourism growth and resilience.